Annual Bluegrass (Poa annua) Control with Methiozolin and Nutrient Tank-Mixtures. (17th August 2017) - Flessner, Michael L.; McElroy, J. Scott; McCurdy, James D.
Abstract : Methiozolin is a selective herbicide that has been reported to control annual bluegrass in creeping bentgrass putting greens. Golf course managers frequently tank-mix fertilizers with herbicides to reduce time and labor, but no information is available regarding such mixtures with methiozolin. Research was conducted to evaluate methiozolin for annual bluegrass control and creeping bentgrass safety when tank-mixed with ammonium sulfate or iron sulfate. Mixtures with ammonium sulfate did not influence annual bluegrass control while they did reduce creeping bentgrass injury in some instances. Mixtures with iron sulfate varied by experimental run but annual bluegrass control was either similar or increased while creeping bentgrass injury did not vary. Paclobutrazol was included as an alternative agrochemical comparison for annual bluegrass management; its application resulted in similar control and injury with and without iron sulfate addition, and injury and control were similar to methiozolin at appropriate rates. While some differences were observed, overall annual bluegrass and creeping bentgrass response to methiozolin was not affected by tank-mix nutrient partner relative to methiozolin applied alone.